Suicidal Ideations and Behavior in Patients With Young and Late Onset Dementia - Ortner, Marion; Riedl, Lina; Jox, Ralf J.; Hartmann, Julia; Roßmeier, Carola; Dorn, Bianca; Kehl, Victoria; Egert-Schwender, Silvia; Fischer, Julia; Diehl-Schmid, Janine (Frontiers in Neurology, 2021)
Background and Objectives: Data on suicidal ideation, behavior and the risk factors in patients with dementia is scarce. To evaluate the prevalence of death wishes, suicidal ideation, and suicidal behavior of young (YOD) and late onset dementia (LOD) and to identify risk factors for suicidal ideation and behavior. Methods: We interviewed 157 family caregivers of patients with advanced dementia using questions from the Columbia-Suicide Severity Rating Scale to gather information about suicidal ideation and behavior before the onset of symptoms of dementia, after the onset of dementia and within 30 days prior to the interview. At the time of the interview, we also assessed disease severity, cognitive function, and other psychological, behavioral and physical symptoms of the patients as well as the caregivers’ psychological wellbeing. Results: 44 (28%) of the patients expressed suicidal ideation or behavior at some time after the onset of symptoms, and 14 (9%) of these within the month prior to the assessment. Two patients had attempted suicide after the onset of dementia. There were no statistically significant differences between patients with and without suicidal ideations or behavior with regards to demographics or age at onset of dementia. In patients with advanced dementia, Alzheimer’s disease (rather than frontotemporal lobar degeneration), better cognitive function, more severe psychological, behavioral, and physical symptoms, and a reduced quality of life were associated with the expression of suicidal ideation. Conclusions: According to caregivers’ reports, majority of patients with dementia did not express suicidal ideation or show suicidal behavior. Patients who expressed suicidal ideation during early stages of dementia often stopped expressing them in advanced stages. It remains unclear if this was due to reduced communication abilities, a reduction of disease awareness, and/ or an adjustment to their situation.